ANALISIS KOMPOSISI JENIS DAN KEPADATAN MAKROZOOBENTOS PADA EKOSISTEM PERAIRAN DANAU SERANTANGAN SINGKAWANG - Lukmansyah, Nisrina Nabila; Munir, Ahmad Mulyadi Sirojul; Anzani, Yunita Magrima (Jurnal Sains Pertanian Equator, 2025)
Serantangan Lake is a post-mining lake located near an active illegal gold mining area, thus requiring an assessment of its water quality and ecological feasibility. This study aimed to identify the taxa, composition, and density of macrozoobenthos. The research was conducted from December 2024 to February 2025 at three stations using purposive sampling. Samples were collected from 8 sampling points, four times, at two-week intervals. A total of 1,078 individual macrozoobenthos were identified, consisting of 14 genera belonging to 14 families and 9 orders: Mesogastropoda, Architaenioglossa, Decapoda, Haplotaxida, Diptera, Coleoptera, Ephemeroptera, Odonata, and Hemiptera. The highest composition at Stations I and II was dominated by Odonata, while Station III was dominated by Haplotaxida (Tubifex sp.). Station I indicated good water quality, characterized by the presence of intolerant taxa such as Baetidae and Tipulidae. Station II reflected moderate quality, with a dominance of semi-tolerant taxa. Station III showed the lowest quality due to the dominance of tolerant taxa and low diversity. Anthropogenic activities, such as fish harvesting and illegal gold mining (PETI), are suspected to be the main factors affecting the macrozoobenthic community structure in the lake.